SMYD2‐mediated TRAF2 methylation promotes the NF‐κB signaling pathways in inflammatory diseases - Weijun Wu (Wiley, 2021)
Abstract Background The methylation of lysine residues has been involved in the multiple biological and diseases processes. Recently, some particular non‐histone proteins have been elucidated to be methylated by SMYD2, a SET and MYND domain protein with lysine methyltransferase activity. Methods SMYD2 was evaluated in synovial tissue and cells derived from rheumatoid arthritis patients. We confirmed TRAF2 could be methylated by SMYD2 using Mass spectrometry, pull‐down, immunoprecipitation, methyltransferase assay, ubiquitination assay, luciferase reporter assays, and western blot analyses. Using loss‐ and gain‐of function studies, we explored the biological functions of SMYD2 in vitro and in vivo. Using acute and chronic inflammation with different mice models to determine the impact of SMYD2. Results Here, we first time confirmed that the cytoplasmic protein TRAF2 as the kernel node for NF‐κB signaling pathway could be methylated by SMYD2. SMYD2‐mediated TRAF2 methylation contributed to the durative sensitization of NF‐κB signaling transduction through restraining its own proteolysis and enhancing the activity. In addition, we found knocking down of SMYD2 has different degrees of mitigation in acute and chronic inflammation mice models. Furthermore, as the lysine‐specific demethylase, LSD1 could resist methylation on TRAF2 induced by SMYD2. Conclusions Our data uncovered an unprecedented cytoplasmic protein network that employed methylation of TRAF2 for the maintenance of NF‐κB activation during inflammatory diseases.